(untitled) (MUST JOURNAL OF RESEARCH AND DEVELOPMENT, 2025)
The Tanzania National Roads Agency (TANROADS) is a semi-autonomous agency under the Ministry of Works and Transport, responsible for the planning, construction, maintenance, and management of trunk and regional roads across Tanzania Mainland. Its mandate also includes airport development, operation of weighbridges, and supervision of road projects. Despite these responsibilities, TANROADS projects continue to suffer from persistent issues such as cost overruns, time delays, and substandard construction quality. This review aims to critically assess how weaknesses in the tendering and supervision processes contribute to project underperformance and to identify practical reforms. A systematic literature review was conducted, drawing on 45 sources published between 2010 and 2024, including academic studies, CAG audit reports, procurement laws, and institutional publications. Thematic analysis was used to identify common challenges and proposed solutions. Tendering challenges include poor feasibility planning, weak tender documentation, non-adherence to evaluation criteria, and delays in contract signing. These often result in the selection of under-qualified contractors and inefficient project execution. Recommended reforms include mandatory feasibility studies, evaluator training, stricter use of the National e-Procurement System (NeST), and adoption of performance-based evaluation frameworks. In the supervision phase, key challenges include inadequate staffing, irregular site inspections, weak documentation, poor stakeholder coordination, and limited enforcement capacity. To address these, the review recommends increasing personnel supervision, digitizing field reporting, standardizing procedures, and implementing post-project performance evaluations.